2020
DOI: 10.1002/pssa.202000281
|View full text |Cite
|
Sign up to set email alerts
|

Wake‐Up Mechanisms in Ferroelectric Lanthanum‐Doped Hf0.5Zr0.5O2 Thin Films

Abstract: Since the discovery of ferroelectricity in thin doped hafnium oxide layers, there is a rapidly growing interest in the implementation of this material into nonvolatile memory devices such as ferroelectric capacitors, transistors, or tunnel junctions. In most cases, a field‐cycling‐induced change in the remanent polarization is attributed to wake‐up and fatigue in ferroelectric HfO2 devices. The lanthanum‐doped hafnium/zirconium mixed oxide system is of broad interest due to its high endurance stability and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…This phase transition is related to the wake-up effect in ferroelectricity, as reported in the previous studies. [12,[16][17][18][19][20] Although the ferroelectric properties stem from the orthorhombic structure, the orthorhombic structure in the as-deposited or as-annealed film is not needed for exhibiting ferroelectricity. Thus, structural changes by the electric field, including phase transition and domain switching, play a key role in fluorite oxide-based ferroelectric materials, and studies on epitaxial films are a suitable platform to clarify these phenomena.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase transition is related to the wake-up effect in ferroelectricity, as reported in the previous studies. [12,[16][17][18][19][20] Although the ferroelectric properties stem from the orthorhombic structure, the orthorhombic structure in the as-deposited or as-annealed film is not needed for exhibiting ferroelectricity. Thus, structural changes by the electric field, including phase transition and domain switching, play a key role in fluorite oxide-based ferroelectric materials, and studies on epitaxial films are a suitable platform to clarify these phenomena.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] In particular, HfO 2 -based materials often require a certain number of electric field cycles to exhibit ferroelectricity. [12][13][14][15][16][17][18][19] Particularly, this so-called wakeup effect relates to the structural change in the electric field. Previous studies have shown a 90 domain rotation from inplane to out-of-plane polarizations using scanning transmission electron microscopy (STEM), selected area electron diffraction, and microarea X-ray diffraction (XRD) studies.…”
Section: Introductionmentioning
confidence: 99%
“…This hinders a comprehensive solution to the problem. For wake-up, three main mechanisms have been proposed: field-driven phase change, where the nonpolar tetragonal phase (T-phase) and monoclinic phase (M-phase) convert to the polar O-phase during cycling; , domain depinning caused by the redistribution of trapped charges, including oxygen vacancies; ,, and rotation of the initially in-plane aligned ferroelectric domains to the out-of-plane direction . Evidence of phase change has previously been obtained via in situ high-resolution transmission electron microscopy (HRTEM), in which evidence of a structural transformation from T-phase to O-phase during electric field cycling has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…A domain-depinning mechanism was supported by a range of electrical measurements. Through temperature-dependent voltage cycling measurements, Mehmood et al suggest that the wake-up can be separated into two stages: charge redistribution and ferroelectric domain depinning, followed by a phase change in the electrode interfacial regions after 10 4 cycles . In contrast, by means of synchrotron XRD and scanning transmission electron microscopy (STEM), Shimizu et al revealed ferroelastic domain switching as a contributor to wake-up during the initial application of an electric field on an epitaxial film .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the crystallization temperature is highly relevant to the wakeup process. [13,[15][16][17] In particular, a high crystallization temperature could effectively render wake-up-free ferroelectric capacitors based on HZO. [17] Therefore, raising the processing temperature is a potential solution to get rid of the wake-up phenomenon.Nevertheless, using high crystallization temperature leads to other serious problems.…”
mentioning
confidence: 99%